True crime and women: writers, readers, and representations - Pâquet, Lili; Williamson, Rosemary (Routledge studies in crime, media and culture, 2025)
"Bringing new research from true crime writers, scholars, and media practitioners around the world, this book offers fresh perspectives on how women read, write, and are portrayed in true crime stories across different platforms, including documentaries, podcasts, and TikToks. The genre of true crime is flourishing, and it is overwhelmingly consumed by women. Despite this, there is much we do not know about how women consume true crime and are represented in true crime stories of various kinds. This edited volume helps to fill this gap in our knowledge. Across 10 chapters and using a variety of study methods, including creative practice, interviews, surveys, archival research, and case studies, the book reveals the multifaceted ways that true crime matters to women and suggests areas of future research. It also offers new insights on a diverse range of topics, such as racial identities, fraudsters, activism, victimization, and deviance, as well as highlights major cases from past to present which have influenced criminal justice responses. True Crime and Women is intended for researchers and students of criminology, literary studies, gender studies, media and journalism studies, and rhetorical studies, as well as media practitioners and writers"--